Breaking of Thermopower–Conductivity Trade‐Off in LaTiO3 Film around Mott Insulator to Metal Transition. Issue 23 (21st October 2021) - Katase, Takayoshi; He, Xinyi; Tadano, Terumasa; Tomczak, Jan M.; Onozato, Takaki; Ide, Keisuke; Feng, Bin; Tohei, Tetsuya; Hiramatsu, Hidenori; Ohta, Hiromichi; Ikuhara, Yuichi; Hosono, Hideo; et al.
Abstract: Introducing artificial strain in epitaxial thin films is an effective strategy to alter electronic structures of transition metal oxides (TMOs) and to induce novel phenomena and functionalities not realized in bulk crystals. This study reports a breaking of the conventional trade‐off relation in thermopower ( S )–conductivity ( σ ) and demonstrates a 2 orders of magnitude enhancement of power factor (PF) in compressively strained LaTiO3 (LTO) films. By varying substrates and reducing film thickness down to 4 nm, the out‐of‐plane to the in‐plane lattice parameter ratio is controlled from 0.992 (tensile strain) to 1.034 (compressive strain). This tuning induces the electronic structure change from a Mott insulator to a metal and leads to a 10 3 ‐fold increase in σ up to 2920 S cm −1 . Concomitantly, the sign of S inverts from positive to negative, and both σ and S increase and break the trade‐off relation between them in the n‐type region. As a result, the PF (= S 2 σ ) is significantly enhanced to 300 µW m − 1 K −2, which is 10 2 times larger than that of bulk LTO. Present results propose epitaxial strain as a means to finely tune strongly correlated TMOs close to their Mott transition, and thus to harness the hidden large thermoelectric PF. Abstract : Thermoelectric power‐factor enhancement by 2 orders of magnitude is discovered beyond the Mott insulator to metal transition in compressively strained LaTiO3 films. Both conductivity and thermopower increase in the n‐type region, breaking the conventional trade‐off between them. Tuning oxides close to their Mott transition through epitaxial strain is proposed for harnessing large power factors.